Advances in information storage systems - Bhushan, Bharat (Word scientific Publishing, 1995)
Includes bibliographical references; The series Advances in Information Storage Systems covers a wide range of interdisciplinary technical areas, related to magnetic or optical storage systems. The following nonexhaustive list is indicative of the scope of the topics: Friction, Adhesion, Wear and Lubrications, Coatings, Solid Mechanics, Air Flow, Contamination, Instrumentation, Dynamics, Shock and Vibration, Controls, Head and Suspension Design, Actuators, Spindle and Actuator Motors and Bearings, Structure of Thin Films, Corrosion, Long-Term Reliability, Materials and Processing, Manufacturing and Automation, Economics. This volume contains 30 articles covering various aspects of the information storage and processing industry. It is organized into three parts: Mechanics and Tribology of Magnetic Rigid Disk Drives; Dynamics and Controls of Magnetic Rigid Disk Drives; and Mechanics of Flexible Media Systems